Xenophon's Sparta : an introduction - Proietti, Gerald. (Mnemosyne, Supplements, 1987)
Xenophon is usually believed to have written his Hellenica as a general ''history of his own times'' in Greece, and is criticized for his disproportionately close attention to Spartan affairs and his apparent bias in favour of the Spartans. But his treatment of Sparta is much more coherent and purposive than has been noticed; and knowing the cirumstances of his life, we should consider that there were ample reasons of prudence (at least) for him to have written with much circumspection about Sparta and especially about Agesilaus and Agesilaus' friends. This methodical interpretative study of Lysander in the Hellenica as well as of the Polity of the Lacedaemonians demonstrates that Xenophon wrote aobut this city - famous for the communal life of its citizens - with critical and philosophic intent. As a case study in reading classical history, it might signal the need for a complete reevaluation of other historians as well.